Determinants of sucess and failure in internationalisation of the cork business : a tale of two iberian family firms - Branco, Amélia (2015)
The trajectories of internationalisation followed by family firms can be viewed from several theoretical approaches: phases and models of the internationalisation process; international entrepreneurship, the sociological perspective and family business theory. A historical perspective of internationalised family firms, allowing for the integration of the abovementioned approaches, is useful to obtain a deep understanding of the internationalisation process of different sectors and of different countries. The main purpose of this paper is to identify the facilitating and restricting factors during the internationalisation path of family firms, whilst considering the influence in their competitive advantages, of ownership structure, management attitudes and other intangible assets, as well as external factors to the firms, like location. The research involved a long run analysis (of more than one century) of two firms which operate in the cork business in Spain and Portugal: Mundet & C.ª, Lda and Corticeira Amorim. One of these companies - Mundet - was closed down in the 1980s and the other – Corticeira Amorim – became, and still is, the leading firm worldwide in the cork industry. A detailed comparison of these two histories - one of failure, and the other of success - permits an accurate identification of the determinants of successful internationalisation. In fact, this comparison is useful for understanding several characteristics of both firms, some of which are similar and others which are different, allowing to test several hypotheses within the context of the theoretical approach of the internationalisation of family firms. This methodological option can be justify by several aspects. Firstly, both are family firms operating in the same business and both were concentrated on the foreign market since their conception. Secondly, both their histories encompass most of the 20th Century and both faced similar national and international constraints, which were overcome, as they both ended up becoming the leading firms in the cork business, although at different periods of time. Thirdly, their choices of location were different and, although in both cases they benefitted from agglomeration forces during certain phases of the business, location was an important determinant of the opposing destinies of these two emblematic cork family firms from Iberia.